Hypothyroidism in vasculitis. (3rd November 2021) - Kermani, Tanaz A; Cuthbertson, David; Carette, Simon; Khalidi, Nader A; Koening, Curry L; Langford, Carol A; McAlear, Carol A; Monach, Paul A; Moreland, Larry; Pagnoux, Christian; Seo, Philip; Specks, Ulrich; et al.
Abstract: Objective: To study the prevalence, risk and clinical associations of hypothyroidism among several forms of vasculitis. Methods: Patients with GCA, Takayasu's arteritis (TAK), PAN and the three forms of ANCA-associated vasculitis [AAV; granulomatosis with polyangiitis (GPA), microscopic polyangiitis and eosinophilic granulomatosis with polyangiitis (EGPA)] enrolled in a prospective, multicentre, longitudinal study were included. Results: The study included data on 2085 patients [63% female, 90% White] with a mean age of 54.6 years (s .d . 17.2). Diagnoses were GCA (20%), TAK (11%), PAN (5%), GPA (42%), microscopic polyangiitis (8%) and EGPA (14%). Hypothyroidism was present in 217 patients (10%) (83% female), with a mean age 59.8 years (s .d . 14.5). Age- and sex-adjusted risk of hypothyroidism was GCA, odds ratio (OR) 0.61 (95% CI 0.41, 0.90); TAK, OR 0.57 (95% CI 0.31, 1.03); PAN, OR 0.59 (95% CI 0.25, 1.38); GPA, OR 1.51 (95% CI 1.12, 2.05); microscopic polyangiitis, OR 1.81 (95% CI 1.18, 2.80) and EGPA, OR 0.82 (95% CI 0.52, 1.30). Among patients with AAV, age- and sex-adjusted risk of hypothyroidism was higher with positive MPO-ANCA [OR 1.89 (95% CI 1.39, 2.76)]. The clinical manifestations of vasculitis were similar in patients with and without hypothyroidism, except transient ischaemic attacks, which were more frequently observed in patients with GCA and hypothyroidism (12% vs 2%; P = 0.001). Conclusions: Differences in the risk of hypothyroidism among vasculitides may be due to genetic susceptibilities or immune responses. This study confirms an association of hypothyroidism with MPO-ANCA.